2007
DOI: 10.1080/00016340701472773
|View full text |Cite
|
Sign up to set email alerts
|

Precision, consistency, and reproducibility of blood pressure in diabetic and non‐diabetic pregnancy: the appraisal of repeated measurements

Abstract: A monitor (Spacelab 90207) was compared with sphygmomanometric blood pressure (BP) with respect to reproducibility and variations on precision and consistency. Some 133 women with type 1 diabetes mellitus and 59 non-diabetic women were recruited. During pregnancy, systolic BP was between 6 and 12 mmHg higher in the oscillometric than the auscultatory readings, and diastolic BP was between 1 and 2.6 mmHg. The association of difference with the mean BP disappeared with progression of pregnancy and the repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The remaining studies reported measurements at a single time. A manual sphygmomanometer was used in fifteen studies [34, 35, 37–39, 41, 44, 45, 47, 49, 53, 57, 58, 62, 64]. An automated blood pressure monitor was used in thirteen studies [32, 33, 42, 43, 48, 5052, 5456, 59, 61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies reported measurements at a single time. A manual sphygmomanometer was used in fifteen studies [34, 35, 37–39, 41, 44, 45, 47, 49, 53, 57, 58, 62, 64]. An automated blood pressure monitor was used in thirteen studies [32, 33, 42, 43, 48, 5052, 5456, 59, 61].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported that the measurement device was calibrated prior to the study taking place (all manual sphygmomanometer methods) [37, 39, 44, 62, 64]. The method of blood pressure measurement was not specified in six studies [31, 35, 36, 40, 46, 69]. Use of an appropriately sized BP cuff was reported in 13 studies [33, 37, 38, 4245, 47, 49, 54, 58, 61, 62].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we found very few studies analyzing the validity of automatic blood pressure monitors in a population with noninsulin-dependent type 2 diabetes, [37,[45][46][47][48], and furthermore, most of these validations did not follow specific protocols such as ESH-IP2 [9-11].…”
Section: Discussionmentioning
confidence: 99%
“…Other variables that can influence blood pressure assessment are the time of day, prior food intake, caffeine use, smoking, exercise, patient's position, automated versus manual equipment, and even the temperature of the room. 2 Blood pressure should ideally be taken with the woman in a comfortable seated position and the arm resting at the level of the heart. 3 Neither the woman nor the examiner should be talking while the blood pressure is being taken.…”
mentioning
confidence: 99%
“…2 Blood pressure should ideally be taken with the woman in a comfortable seated position and the arm resting at the level of the heart. 3 Neither the woman nor the examiner should be talking while the blood pressure is being taken.…”
mentioning
confidence: 99%